2019
DOI: 10.3389/fphar.2019.01353
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Network Pharmacology Analysis of Classical TCM Prescriptions for Chronic Liver Disease

Abstract: Chronic liver disease (CLD) has become a major global health problem while herb prescriptions are clinically observed with significant efficacy. Three classical Traditional Chinese Medicine (TCM) formulae, Yinchenhao Decoction (YCHT), Huangqi Decoction (HQT), and Yiguanjian (YGJ) have been widely applied in China to treat CLD, but no systematic study has yet been published to investigate their common and different mechanism of action (MOA). Partial limitation may own to deficiency of effective bioinformatics m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…This means that most real-world clinical prescriptions would tend to have a high degree of herbal combinations as good as those of TEFD prescriptions. It is practical and reasonable that, in TCM clinical settings, most practitioners would directly adopt the classical prescriptions or use the classical prescriptions as a basic therapeutic framework for clinical treatments ( Duan et al, 2018 ; Chen et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…This means that most real-world clinical prescriptions would tend to have a high degree of herbal combinations as good as those of TEFD prescriptions. It is practical and reasonable that, in TCM clinical settings, most practitioners would directly adopt the classical prescriptions or use the classical prescriptions as a basic therapeutic framework for clinical treatments ( Duan et al, 2018 ; Chen et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, integrated network pharmacology and metabolomics have been widely used to investigate the mechanism of action of TCMs, such as the antidepressant mechanisms of Xiaoyaosan ( Liu et al, 2021 ) and detoxification mechanisms of Yunnanbaiyao ( Ren et al, 2020 ). Several successful metabolomics or network pharmacology tests on the anti-liver fibrosis mechanism of TCMs have been reported ( Chen et al, 2019 ; Xiong et al, 2020 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacological studies have shown that YCHD can treat chronic liver diseases through functional modules such as immune response, inflammation, energy metabolism, and so on. However, compared with Huangqi decoction for qi deficiency syndrome, YCHD has unique functional modules related leptin-induced complement pathway and leukocyte migration across the endothelium, which may correlate with the anti-inflammatory effects [27].…”
Section: Discussionmentioning
confidence: 99%